PERANCANGAN SISTEM INFORMASI E-SPORTS DI INDONESIA (KHUSUSNYA MOBILE LEGENDS) BERBASIS WEBSITE MENGGUNAKAN METODE OOAD (OBJECT ORIENTED ANALYSIS DESIGN) - Anas Nasrullah Nasrull; Sewaka (CV. Multi Kreasi Media, 2022)
In this study, the goal is to design a web-based information system for eSports in the Mobile Legends Bang-Bang (MLBB) division in Indonesia. Where the world of eSports is currently in great demand by people in Indonesia, especially teenagers. The method used in this study uses Object Oriented Analysis and Design (OOAD), This method is a new way of thinking about a problem by using a model created according to real-world concepts. The basis of creation is an object which is a combination of data structure and behavior in a Entity Concepts (OOAD) includes the analysis and design of a system with an object approach. So the results of the study can be concluded that a website-based information system on the eSports division of the Mobile Legends Bang-Bang (MLBB) is expected to make it easier for people in Indonesia to know about eSports in the Mobile Legends division. This system displays a list of eSports teams (MLBB), a list of players, schedules and information. On the other hand, the interest in eSports in the Mobile Legends Bang-Bang division is quite high based on predetermined criteria. The suggestion is that those who have an interest in eSports can be guided and directed, so that they can play well.